The role of epigenetics in respiratory health in urban populations in low and middle-income countries. (2019) - Robertson, Nicole M.; Kayongo, Alex; Siddharthan, Trishul; Pollard, Suzanne L.; Villalobos, Jose Gomez; Ladd-Acosta, Christine; Kirenga, Bruce; Checkley, William
Abstract: As urbanization increases in low- and middle-income countries (LMICs), urban populations will be increasingly exposed to a range of environmental risk factors for non-communicable diseases. Inadequate living conditions in urban settings may influence mechanisms that regulate gene expression, leading to the development of non-communicable respiratory diseases. We conducted a systematic review of the literature to assess the relationship between respiratory health and epigenetic factors to urban environmental exposures observed in LMICs using MEDLINE, PubMed, EMBASE, and Google Scholar searching a combination of the terms: epigenetics, chronic respiratory diseases (CRDs), lung development, chronic obstructive airway disease, and asthma. A total of 2835 articles were obtained, and 48 articles were included in this review. We found that environmental factors during early development are related to epigenetic effects that may be associated with a higher risk of CRDs. Epigenetic dysregulation of gene expression of the histone deacetylase (HDAC) and histone acetyltransferase gene families was likely involved in lung health of slum dwellers. Respiratory-related environmental exposures influence HDAC function and deoxyribonucleic acid methylation and are important risk factors in the development of CRD. Additional epigenetic research is needed to improve our understanding of associations between environmental exposures and non-communicable respiratory diseases.